Quality Stability of Spent Laying Hen Patties Supplemented with Lemongrass Powder During Refrigerated Storage for Sustainable Meat Product Development - Nimas Dwi Sukmawardani; Herly Evanuarini; Dedes Amertaningtyas; Ria Dewi Andriani; Eko Widodo (Postgraduate, University of Mataram, 2026)
Spent laying hen meat processed into patties is susceptible to quality deterioration during refrigerated storage. This study evaluated the physicochemical, microbiological, and sensory characteristics of spent laying hen patties supplemented with 1.50% lemongrass powder during refrigerated storage at 4.00°C. Observations were conducted on days 0, 7, 14, and 21. The analyzed parameters included pH, peroxide value, color (L*, a*, b*), texture, moisture content, Total Plate Count (TPC), and sensory attributes. Statistical evaluation was performed using analysis of variance (ANOVA), with Duncan’s Multiple Range Test applied for multiple comparisons among storage periods. Storage duration significantly affected all observed parameters (p<0.01). During storage, pH increased from 5.56 to 6.08, peroxide value increased from 0.67 to 1.51 meq/kg, moisture content increased from 56.28% to 59.54%, and TPC increased from 1.71 to 2.82 log CFU/g. In contrast, texture decreased from 11.31 to 8.27 N, accompanied by reductions in color and sensory acceptance scores. Overall, the addition of 1.50% lemongrass powder helped maintain the physicochemical, microbiological, and sensory quality of spent laying hen patties, particularly up to 14 days of refrigerated storage, supporting the development of sustainable meat products with added value.